Automatic Resonance-Frequency Tuning and Tracking Technique for a 1MHz Ultrasonic-Piezoelectric-Transducer Driving Circuit in Medical Therapeutic Applications Using dsPIC Microcontroller and PLL Techniques - Suttipong Boontaklang; Chow Chompoo-Inwai (My University, 2019)
Driving ultrasonic piezoelectric transducer (UPZT) at maximum performance in real-time operations is a very challenging task due to the deterioration problem of ultrasound output causing by human-skin impedance fluctuations.This paper proposed ideas and solutions on how to maximize the UPZT driving circuit performance in or deter to solve the deterioration problem.A newly-designed feedback control block with a phase-locked-loop (PLL) technique controlled by microcontroller has been added to the conventional UPZT driving circuit to ensure the automatic resonance frequency tuning and tracking capabilities.After intensive experiments, it is clear that the proposed technique works flawlessly and much more efficient compared to the conventional one.The experimental results also confirm that the percentage of error in tuning to the desired frequency is less than ±0.2% and the speed of tuning convergence time is between 9-12 milliseconds on average.
Keywords: Innovative Energy Harvesting Technologies